MARYAM AL-ʿIJLIYA AND HER SCIENTIFIC LEGACY (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the scientific and practical contributions of thefemale astrolabe maker referred to in the historical sources as al-ʿIjliya and widelyknown in modern literature as Maryam al-Usturlabi. Drawing primarily on the tenthcentury bio-bibliographical work Al-Fihrist by Ibn al-Nadim, and situating its evidencewithin the broader history of the astrolabe and of astronomy in Islamic civilization, thestudy reconstructs the intellectual and courtly environment in which she worked at thecourt of the Hamdanid emir Sayf al-Dawla in Aleppo. The article examines the Greekorigins and Islamic development of the astrolabe, its construction and its religious andpractical functions, the place of women in the scientific culture of medieval Islam, andthe documentary basis for what can responsibly be said about al-ʿIjliya herself. It arguesthat, although the surviving record concerning her is extremely limited, her recognizedmastery of one of the most demanding of the mathematical crafts marks her as a figureof genuine historical importance and as an enduring symbol of the participation ofwomen in science.
Keywords: al-ʿIjliya; Maryam al-Usturlabi; astrolabe; Islamic astronomy; ʿilm almiqat; Sayf al-Dawla; Hamdanid Aleppo; women in science; Al-Fihrist.